Metode Belajar Membaca Tanpa Mengeja (BMTM); Alternatif Untuk Meningkatkan Kemampuan Membaca Permulaan Anak Dyslexia - Kania Mandala; Elsa Efrina (PAKAR Pendidikan, 2019)
This research is motivated by the reading ability of children with learning difficulties that are still low, so that the result of this child cannot follow learning optimally due to these limitations. The purpose of this study was to prove the effect of learning methods of reading without spelling (BMTM) on improving the ability to read the beginning of a child's learning difficulties. The research subjects were children of learning difficulties with female age 8 years who attended Semen Padang 1 Elementary School, Indarung, Lubuk Kilangan, Padang. This study uses the type of Single Subject Research approach with AB design which analyzes the comparison between the baseline results (before intervention is given) and the results of the intervention (when given treatment). Data collection is done by direct observation using the type of measurement, namely the percentage (%) with the data recording tool using a data collection format that is a test instrument in the form of a checklist. Data analysis techniques use graphical visual analysis. The results of this study prove that the ability to read the beginning of children who have learning difficulties has increased after the intervention using the method (BMTM).